Hospital-based Perinatal Outcomes and Complications in Teenage Pregnancy in India - Mukhopadhyay, Prianka (International Centre for Diarrhoeal Disease Research, Bangladesh, 2010)
Teenage pregnancy is a worldwide problem bearing serious social and medical implications relating to maternal and child health. A cross-sectional observational study was undertaken to compare the different sociodemographic characteristics and perinatal outcomes of teenage primigravida mothers with those of adult primigravida mothers in a tertiary-care hospital in eastern India. A sample of 350 each in cases and comparison group comprised the study subjects. Data were collected through interviews and by observations using a pretested and predesigned schedule. Results revealed that the teenage mothers had a higher proportion (27.7%) of preterm deliveries compared to 13.1% in the adult mothers and had low-birth-weight babies (38.9% vs 30.4% respectively). Stillbirth rate was also significantly higher in teenage deliveries (5.1% vs 0.9% respectively). The teenage mothers developed more adverse perinatal complications, such as preterm births, stillbirths, neonatal deaths, and delivered low-birthweight babies, when compared with those of the adult primigravida mothers. Teenage pregnancy is still a rampant and important public-health problem in India with unfavourable perinatal outcomes and needs to be tackled on a priority basis.